Sex Disparities in Sentencing and Judges’ Beliefs: A Vignette Approach - Yan, Shi (Victims & offenders, 2022)
The predominant theories on courtroom decision-making explain extralegal disparities with the courtroom actors’ use of stereotypes. We conducted a vignette study on a sample of judges at the Chinese National Judges College, manipulated the sex of the defendant in each vignette, then asked the subjects for the recommended sentence. The survey also contained a series of questions on the beliefs about the causes of crime, the patterns of criminal behaviors, and the effectiveness of punishment. We found that the judges recommended significantly less harsh sentences for the female homicide defendant, but recommended significantly harsher sentences for both female defrauding and drug trafficking defendants. We also found little evidence that the perception and belief variables were confounders behind the observed sex disparities.